Application For Marriage Dispensation Post Application Of Law Number 16 Year 2019 Concerning Marriage In Jombang - Maya Shofia; Muhammad Andri (Jurnal Penegakan Hukum Indonesia, 2022)
The applicable law has also been updated to adapt to the current situation and time, if it is deemed irrelevant then the applicable law will be abolished and replaced. With the new law, there will be impacts that arise both in society and in law enforcement officials. Consideration of the decision of the Religious Courts in adjudicating cases of marriage dispensation must also be in accordance with the evidence and testimony submitted during the trial so as not to injure the applicable law. The purpose of this study is to find out how effective the application for marriage dispensation is after the enactment of Law Number 16 of 2019. And how is the legal basis for adjudicating marriage dispensation cases at the Jombang Religious Court. This study uses descriptive qualitative research and a sociological approach is applied through data and statements obtained from the interaction between the researcher, the object under study, and the people in the research place. The results of this study indicate that the enactment of Law Number 16 of 2019 has an impact on the Religious Courts by increasing the number of requests for cases of filing early marriage dispensations, many factors have influenced this increase based on the provisions of PERMA Number 5 of 2019 which regulates the procedure for adjudicating Early marriage dispensation cases so that the current trial is more complicated than before.